Physical Properties of Zinc Doping on the Nanostructured Fe₂O₃ Thin Films Deposited by Chemical Spray Pyrolysis Technique - Nazar Abdulmahdi Jabir; Hiba Saad Rasheed; Rushdi Ibrahim Jassim (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study systematically examines the influence of zinc doping (0, 1 and 3 %) on the Physical Properties properties of nanostructured Fe₂O₃ thin films deposited via chemical spray pyrolysis (CSP). (XRD analysis confirms the formation of the hexagonal polycrystalline Fe₂O₃ phase with a preferred (204) orientation. Incorporating zinc enhances the grain size from 11.26 nm in the Pure film to 15.72 nm at 3% Zn, while simultaneously reducing the dislocation density by 27% (from 55.41 to 40.42 × 10¹⁴ lines/m²) and lattice strain by 35% (from 15.75 to 10.21 × 10⁻⁴), indicating a notable improvement in crystalline quality. AFM shows that Zn doping refines the surface morphology, decreasing average roughness from 6.37 to 3.65 nm and reducing grain size from 74.12 to 50.81 nm. Optically, zinc incorporation lowers transmittance while increasing the absorption coefficient. and narrows the bandgap from 2.30 to 2.20 eV. Additionally, both the extinction coefficient and refractive index decrease with doping.